Of Beasts and Bees: the View of the Natural World in Virgil's Georgics and John's Apocalypse - McDonough, Sean M. (New Testament studies, 2000)
The article proposes a dialogue between Virgil's Georgics and John's Apocalypse as a means of illuminating Revelation's view of the natural world. A comparison of the two works reveals a common understanding of the natural order as at once beautiful and terrifying, majestic and vulnerable. While irreconcilable religious differences remain (particularly concerning the figure of Augustus), the two works can still be read in a complementary way. Virgil's lyrical evocations of the Italian countryside give a new depth to the tragedy of the destruction of the natural order in Revelation, while John's theology of hope supplies a theological focus lacking in the Latin poet.